Microencapsulation of hydrogen peroxide for the development of a dental whitening gummy candy and in vitro evaluation using a colorimetric method - Lisa M Caballero; Lucia Ferrari; Mario L Aimar; Ana P Zogbi; Luisina Lavari; Ana M Vázquez (Facultad de Farmacia, Universidad de Granada, 2021)
ABSTRACT Introduction: The appearance and color of the teeth are common concerns for patients and are associated with an increased need for treatments that can improve dental aesthetics. For this reason, in the past 20 years, dental science has been searching for new techniques and materials able to reduce dental discoloration. Method: Gummy candies containing two different concentrations (7% and 14% w/v) of hydrogen peroxide microencapsulated by ionic gelation were prepared. In vitro tooth whitening treatment was carried out for 30 days to test the bleaching action of these formulations. The surface color of the treated teeth was measured using a colorimetric technique. Results: Significant differences were found on comparing the whitening treatments for the two formulations with a control group, with two daily treatments using the formulation with 7% hydrogen peroxide being more effective for whitening than a daily single treatment using the formulation with 14 %. Conclusions: The two formulations developed had an in vitro higher bleaching effect in comparison with the control group, and in addition, better results were achieved if the daily dose was provided by more applications at a lower concentration of hydrogen peroxide.